SOSIALISASI PENERAPAN NILAI – NILAI PANCASILA SILA KE-3 BAGI GENERASI “Z” - Wahyudin, Dian; Chaerunisyah, Ana; Tyas, Indriani Rahayu Ning; Julina, Faizah; Fretes, Mercy Spesa Devina de (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Pancasila, as the foundation of the Indonesian state, emphasizes the importance of applying moral and ethical values in community life. One of the values that is highly relevant to emphasize is the Third Principle, which is "Unity of Indonesia." Socializing the implementation of Pancasila values, particularly the Third Principle, presents a challenge that needs to be overcome, especially in the context of Generation Z living in the era of digitalization and globalization. Generation Z, accustomed to technological advancements, can be directed to understand and apply the Third Principle in their daily lives. Socialization is conducted through engaging approaches in the form of direct interaction. The results of socialization, in the context of implementing the values of the Third Principle, can lead Generation Z to comprehend the diversity of culture, ethnicity, and religion as the nation’s wealth. Understanding the Third Principle fosters a sense of nationalism and patriotism. Generation Z with a strong national consciousness tends to be more committed to common interests and national development. In facing the impacts of technology and information, socializing Pancasila values helps Generation Z filter information, develop critical thinking, and use technology ethically